Exponential Time Trends in a Fractional Integration Model - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper introduces a new modelling approach that incorporates nonlinear, exponential deterministic terms into a fractional integration model. The proposed model is based on a specific version of Robinson's (1994) tests and is more general that standard time series models, which only allow for linear trends. Montecarlo simulations show that it performs well in finite sample. Three empirical examples confirm that the suggested specification captures the properties of the data adequately.
Keywords: C22; C15; 330; exponential time trends; fractional integration; Montecarlo simulations